Co-twinning with fetal Mummification in a Non-Descript Doe: A Case Report - Chaudhary, Neha; Kumar, Arun; Singh, Garima; Kumar, Mohit; sachan, vikas (The Indian Journal of Animal Reproduction, 2024)
A non-descript doe with a pregnancy of approx 4 months with a history of pain symptoms for the last 5 hours, frequent defecation, urination, and blood-tinged vaginal fluid while straining was presented to TVCC, Mathura. The cause of dystocia in the present case was a dead kid in a dorso-transverse position. After evisceration, the kid was delivered and subsequently, one more fetus which was mummified was delivered. The dam was managed with antibiosis, intra-uterine therapy, and uterine ecbolic drug successfully.
Keywords: Doe; Dystocia; Mummification; Co-twin; Dorso-transverse presentation